Assemblage, Environments & Happenings - Kaprow, Allan (New York : Harry N. Abrams Inc. Publishers, 1966)
AY-O ; Brecht, George ; Dewey, Kenneth ; Dine, Jim ; Edelheit, Martha ; Follett, Jean ; Graves, Gloria ; Grooms, Red ; Gutai Group ; Kanayama, Akira ; Kaprow, Allan ; Knizak, Milan ; Kusama Yayoi ; Lebel, Jean Jacques ; Miller, Renee ; Motonaga, Sadamasa ; Mukai, Shuzo ; Murakami, Saburo ; Oldenburg, Claes ; Pollock, Jackson ; Rauschenberg, Robert ; Schmidt, Clarence ; Schmidt, Ruth ; Segal, George ; Shimamoto, Shozo ; Shiraga, Kazuo ; Tanaka, Atsuko ; Tinguely, Jean ; Vostell, Wolf ; Watts, Robert ; Whitman, Robert ; Yamasaki, Tsuruko ; Yoshihara, Michio
Engels
boek